2011
DOI: 10.1095/biolreprod.111.093484
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Suppression of Sertoli Cell Timp2 in Rodents Following Mono-(2-ethylhexyl) Phthalate Exposure Is Regulated by CEBPA and MYC1

Abstract: Our previous studies showed that the prototypical testicular toxic phthalate monoester, mono-(2-ethylhexyl) phthalate (MEHP), suppresses Sertoli cell TIMP2 levels and allows for the activation of MMP2 in seminiferous epithelium. Activation of MMP2 is important for triggering germ cell apoptosis and instigating germ cell detachment from Sertoli cells. These novel findings led us to examine the transcriptional regulation of the Timp2 gene that accounts for the decrease in Sertoli cell TIMP2 levels following MEHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Indeed, it is now assumed that the concomitant transit of preleptotene spermatocytes across the BTB and the release of mature spermatozoa that are permitted by the restructuring of BSTB and apical ES, respectively, are coordinated events involving a local regulatory axis [31]. Supporting this view are the observations that the modification of expression of occludin and the appearance of gaps between Sertoli cells follow MEHP treatment as described in the study of Yao et al [8] and as shown by the dramatic decrease of transepithelial electrical resistance in Sertoli cell cultures treated with MEHP [21]; both studies address the question of the BTB permeability. Because TNF induces COL4A3, MMP9, and TIMP1, but not MMP2, during BTB deassembly [4], it would be interesting to dissect how MEHP can induce MMP2, but not MMP9, and can decrease both TIMP1 and TIMP2 while inducing TNF processing into its soluble form.…”
Section: Mechanisms Of Action Of Phthalates On Seminiferous Epitheliumentioning
confidence: 93%
See 3 more Smart Citations
“…Indeed, it is now assumed that the concomitant transit of preleptotene spermatocytes across the BTB and the release of mature spermatozoa that are permitted by the restructuring of BSTB and apical ES, respectively, are coordinated events involving a local regulatory axis [31]. Supporting this view are the observations that the modification of expression of occludin and the appearance of gaps between Sertoli cells follow MEHP treatment as described in the study of Yao et al [8] and as shown by the dramatic decrease of transepithelial electrical resistance in Sertoli cell cultures treated with MEHP [21]; both studies address the question of the BTB permeability. Because TNF induces COL4A3, MMP9, and TIMP1, but not MMP2, during BTB deassembly [4], it would be interesting to dissect how MEHP can induce MMP2, but not MMP9, and can decrease both TIMP1 and TIMP2 while inducing TNF processing into its soluble form.…”
Section: Mechanisms Of Action Of Phthalates On Seminiferous Epitheliumentioning
confidence: 93%
“…The study by Yao et al [8] represents a significant step forward in our understanding of the molecular events in the testis triggered by MEHP exposure. These findings are of particular importance at this time, given the growing concern about the role played by environmental toxicants on male reproductive function.…”
Section: Mechanisms Of Action Of Phthalates On Seminiferous Epitheliumentioning
confidence: 99%
See 2 more Smart Citations
“…34 This allows for the activation of matrix metalloproteinase 2 (MMP2) in the adluminal space and the consequent production of a soluble form tumor necrosis factor-a (sTNFa), which ultimately induces the increased expression of FasL on Sertoli cells. [34][35][36] Although apoptosis typically does not induce inflammation, recent reports indicate that direct injury to Sertoli cells can change the normal immune privilege environment of the testis (disruption of the blood testis barrier, infiltration of macrophages). 37,38 Therefore, Sertoli cell injury can induce a variety of changes in the seminiferous epithelium including the induction of germ cell apoptosis and altered immune environment.…”
Section: 32mentioning
confidence: 99%